Essays, mainly Shakespearean - Barton, Anne 1933-2013 (Cambridge Univ. Press, 1994)
In a linked but wide-ranging collection the author addresses such diverse issues as Shakespeare's trust (and mistrust) of language, the puzzle of Falstaff's inability to survive in a genuinely comic world, the unconsummated marriage of Imogen and Posthumus in Cymbeline, Shakespeare's debt to Livy and Machiavelli in Coriolanus, 'hidden' kings in the Tudor and Stuart history play; comedy and the city, and deerparks as places of liberation and danger in English drama up to and beyond the Restoration. Professor Barton looks at both major and neglected plays of the period and the ongoing dialogue between them